Bacteriological isolation and characterization of histopathological lesions in tetra bleeding heart (Hyphessobrycon erythrostigma) of the Peruvian Amazon basin - Valera A., Adhemir (2018)
The aim of this study was to determine the presence of bacterial agents and to characterize the histopathological lesions in ornamental tetra bleeding heart (Hyphessobrycon erytrhostigma) fish from a commercial aquarium in the city of Iquitos, Peru. For the microbiological study 60 fish were used, samples were taken from spleen and kidney. Isolation was done on MacConkey agar, Trypticase Soy agar, Pseudomonas Aeromonas selective agar (GSP) and Cytophaga agar and the genus identification was done by Gram staining and biochemical tests. Another 60 fish were used for the histopathological study where the skin, eye, gills, stomach, intestine, liver, spleen, muscle, kidney and peritoneum tissues were analyzed. Seven bacterial genera were isolated: Pseudomonas, Aeromonas, Lactobacillus, Bacillus, Flavobacterium, Staphylocccus and Escherichia. Spores of Mixosporidium sp, hyperplasia and lamella fusion were observed in gills. In the liver and peritoneum, parasitic and bacterial granulomas were found. In muscle, kidney and spleen, bacterial granulomas were found, and in stomach and intestine epithelial cell hyperplasia were found, among other lesions. Results showed that 52.3% (22/42) of the bacterial granulomas were positive for Ziehl Neelsen staining, which showed acid-fast bacilli bacteria. No lesions were found in the eyes.